The sequence given by \(x_0 = a\), \(x_1 = b\) and

\[x_{n + 1} = \frac {1}{2} (x_{n - 1} + \frac {1}{x_n})\]

is periodic. Prove that \(ab = 1\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestMultiply both sides by \(x_n\) for the recursion and get: \(x_{n+1}x_{n}=\frac {1}{2}(x_nx_{n-1}+1)\)

Notice that if we let \(y_n=x_{n}x_{n-1}\), then the recursion becomes: \(y_{n+1}=\frac {1}{2}(y_n+1)\).

It's clear that If \({x_n}\) is periodic, then so is \({y_n}\).

If we let the initial value for sequence \({y_n}\) be \(y_1=ab=c\), then the closed formula for the sequence is: \(y_n=\frac {c-1}{2^{n-1}}+1\). If \(c\) isn't 1, then the sequence either monotonically increases(when \(c<1\))) or decreases (when \(c>1\)) and eventually converges to \(1\). Hence it must be true for \(c=ab=1\).

Log in to reply